Dynamics of single candidate in election of regional heads: Case study in Badung Regency, Bali Province - Widhiasthini, Ni Wayan (International research journal of management, IT and social sciences, 2020)
Badung Regency is one of the regions that hold regional head elections in 2020, to elect the Regent and Deputy Regent. The uniqueness of the Election in Badung Regency is that it is only participated by one pair of candidates or a single candidate. This reality is very contradictory to the condition of the Badung Regency as the richest area in Bali, the center of the economy, and tourism has a geographical structure where all areas can be reached by information technology, as well as an urban area which is inhabited by many immigrants. Based on this, the formulation of the problem discussed is how the dynamics of a single candidate in the regional head election in Badung Regency. The focus of the discussion is the stages of the General Election held by the KPU of Badung Regency in the Badung Regency area. Several research results inspire the discussion of this article. The conclusions that can be formulated include, a single candidate campaign is carried out with several adjustments such as the debate between pairs of candidates being changed to a deepening of the vision and mission to provide political education for the community.